Cancer and Diet - Kenneth Lundstrom (Journal of Pharmacy and Nutrition Sciences, 2012)
Intervention in food intake has been demonstrated to play an enormous role in both prevention and treatment of disease. Numerous studies indicate a clear link between cancer and diet. The substantial development of sequencing technologies has resulted in access to enormous amounts of genomics information, which resulted in the establishment of nutrigenomics as an emerging approach to link genomics research to studies on nutrition. Increased understanding has demonstrated how nutrition can influence human health both at genetic and epigenetic levels. Dramatic dietary modifications have proven essential in reducing risk and even prevention of cancer. Moreover, intense revision of diet in cancer patients has revealed significant changes in gene expression and also has provided therapeutic efficacy even after short-term application. Obviously, a multitude of diets have been evaluated, but probably the common factor for achieving both prophylactic and therapeutic responses is to consume predominantly diets rich in fruits, vegetables, fish and fibers and reduced quantities of especially red meat. Despite encouraging findings on how dietary modifications can prevent disease and restore health, there are a number of factors which complicate the outcome. There are variations in response to dietary changes depending on age and gender. Furthermore, ethnic, social and geographic circumstances play an important role.